DYEING PROPERTIES OF WOOLLEN FABRIC WITH QUERCETIN EXTRACTED FROM PUNICA GRANATUM L. RIND USING DIFFERENT DYEING METHOD AND MORDANT MIXTURES - (:unkn) unknown (UNIV ZAGREB, FAC TEXTILE TECH, 2010)
In our country, there exist about 150 dye plant species that could be used in dyeing; however, these plants are not sufficiently utilized in field cultivation. Through extension of these plants cultivation in agriculture, required raw materials in vegetable dyeing could be met. Hand woven carpets and other products dyed with dye plants are very important income from domestic and foreign tourism sources. The aim of the study was to determine dyeing properties of quercetin, which is extracted from Punica Granatum L. rind, using different mordants and dyeing methods on wool fabrics. The effect of mixture of the tannic acid (TA) and some selected metal salts were investigated in six different dyeing methods by using buffer solutions at pH 6 for 1 h at 98-100 degrees C with closed bath dyeing technique. The colour coordinate of dyed samples were found to lie in the yellow-brown quadrant of the colour space diagram. Colour differences in CIE L*a*b* unit, optimum pH, mordant and dyeing methods of dyed wool fabrics were determined. The rubbing fastness properties for the dyed samples were enhanced by application of mordant salts except Ag2SO4 mordant salt. The light fastness ratings were also improved using all mordant salts as 3-8.
Keywords: punica granatum L.; quercetin; tannic acid; mordant salts; woollen fabric; DIRECT ULTRAVIOLET SPECTROPHOTOMETRY; ASCORBIC-ACID; BACKGROUND CORRECTION; FRUIT JUICES; SOFT DRINKS; VEGETABLES